CONSERVATIVE CARE COST ANALYSIS OF PATIENTS OF LONG BONE FRACTURE IN EMERGENCY ROOM. A REVIEW TO SEE THE SUFFICIENCY OF HEALTH INSURANCE COSTS - Bayusentono Sulis; Cery Taraise Hajali (UNUSA Press, 2020)
INTRODUCTION Long bones are bones that include the humerus, radius, ulna, femur, tibia and fibula. Aside from fibula, the main function of long bones is as the main skeleton in movement. Therefore, whenever there is a fracture in the long bone, the ability to move will be lost.The occurrence of this long bone fracture itself is still a global problem because the number of events is still quite large. This is in line with the increase in socioeconomic status and the incidence of traffic accidents which is one of the causes of fractures. METHOD This study is a prospective study to determine the magnitude of the cost of treatment conservatively in cases of long bone fractures in RSUD dr. Soetomo. The study design used was a prospective cohort. The sample size used in this study was determined by consecutive sampling, ie patients who met the inclusion criteria in the period May - August 2017. RESULTS From the observations for four months from May 2017 - August 2017 at Emergency Room Soetomo General Hospital, found 77 patients with long bone fractures that were casted. Of these patients, 38 patients were placed in a slab, 39 patients were placed in a circular cast. Among the 39 people, 17 patients were excluded according to the exclusion criteria and 22 patients were included as the study sample according to the inclusion criteria. By using a statistical test using paired sample T test with a value of α = 0.05, a significance of 0.025 was obtained. Because the significance value is 0.025 <0.05 (α). DISCUSSION From the resultsa difference between the BPJS rate of installing circular cast on long bone fractures with the real cost of installing circular cast on long bone fractures. In addition, from the value of the mean we get that the average value of the BPJS rate is greater than the real cost value, which means we can conclude that the BPJS cost can cover the cost of conservative therapy in cases of long bone fractures. CONCLUSION In the economic aspect, the longer the length of stay means the higher the costs that must be paid by the patient (the payer) and accepted by the hospital. This only applies to real tariffs, whereas to INACBG's long or short length of stay does not affect the cost.